Kepuasan Masyarakat terhadap Layanan Pemerintah dalam Menurunkan Prevalensi Penyakit Hep-B pada Anak Usia 0-12 Tahun di Indonesia: Public Satisfaction of Government Services in Reducing the Prevalence of Hep-B Disease for Children 0-12 Years in Indonesia - Silvia, Elsa; Rizaldy, Defri (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2023)
This research taken from a substantial and urgent need for the Indonesian especially for children under 0-12 years in Indonesia who still has limit knowledge about Hep-B prevalence. The government has work harder to give health education and awareness in reducing the prevalence of hep-B disease for children 0-12 years in Indonesia. Therefore, the purpose of this study is to see how good the communication strategy is conducted by government of Indonesia and how about the public satisfaction about its services. This study used quantitative method by using an observative, documentative and questionnaire for 220 respondents from several districts in Indonesia as the tools of collecting data. This research concluded that: (a) public services in terms of health education and awareness campaigns in reducing the prevalence of hep-B in children aged 0-12 years was good and satisfying, b) the factors that most influence in increase in the prevalence of Hep-B in children aged 0-12 years are mother-to-child transmission: can occur during pregnancy, childbirth, or breastfeeding and is a common mode of transmission in areas with high prevalence of hep-B and lack of screening, c). what the government can do as a public service in reducing the prevalence of Hep-B in children aged 0-12 years in Indonesia is health education and awareness of hep-B campaign by several ways, such as school-based education, community-based education, mass media campaign, and health worker education.